Review: Democratic Institutions and Long Term Action: Exploring the Institutional Antecedents of Presentism and Intergenerational Justice (PhD by Daan Vermassen, Vrije Universiteit Brussel) - Celis, Karen (Politics of the Low Countries, 2025)
Representative democracies, at least in their current form, are notorious for their bias towards the present and their lack of consideration of the future” (Vermassen, 2023, p. 1, emphasis added). Daan’s PhD deals with democratic short-termism or democratic myopia, one of the key challenges that many, if not all, contemporary democracies face. In response to the threat to intergenerational justice, democratic innovations are put in place to secure the rights of future generations. Similar to the institutional responses to representational problematics of historically disadvantaged groups such as women or ethnic/racialised minorities, solutions are underpinned by a logic of presence. In the case of unborn generations, for obvious reasons, this presence cannot be physical; it is rather engendered through representation, in some form or another, of their interests. This, then, begs questions such as: what are the interests of the ‘future represented’? Are some interests more important than others? How to decide?